2016
DOI: 10.1186/s13059-016-0976-2
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell whole genome sequencing reveals no evidence for common aneuploidy in normal and Alzheimer’s disease neurons

Abstract: BackgroundAlzheimer’s disease (AD) is a neurodegenerative disease of the brain and the most common form of dementia in the elderly. Aneuploidy, a state in which cells have an abnormal number of chromosomes, has been proposed to play a role in neurodegeneration in AD patients. Several studies using fluorescence in situ hybridization have shown that the brains of AD patients contain an increased number of aneuploid cells. However, because the reported rate of aneuploidy in neurons ranges widely, a more sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
137
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 26 publications
7
137
1
1
Order By: Relevance
“…These studies suggest that the level of aneuploidy in brain and liver is much lower than previously reported, with aneuploidy only affecting $2-5% of the cells, similar to the low rates of aneuploidy which were reported for epidermis. [62][63][64] Together these data suggest that many human tissues, including brain, skin and liver, contain a low level of aneuploidy. However, the exact contribution of aneuploid cells to in vivo tissues still needs to be more accurately quantified.…”
Section: How Well Is Aneuploidy Tolerated In Vivo?mentioning
confidence: 76%
“…These studies suggest that the level of aneuploidy in brain and liver is much lower than previously reported, with aneuploidy only affecting $2-5% of the cells, similar to the low rates of aneuploidy which were reported for epidermis. [62][63][64] Together these data suggest that many human tissues, including brain, skin and liver, contain a low level of aneuploidy. However, the exact contribution of aneuploid cells to in vivo tissues still needs to be more accurately quantified.…”
Section: How Well Is Aneuploidy Tolerated In Vivo?mentioning
confidence: 76%
“…On the other hand, in a recent study, a twofold increase in X chromosome aneuploidy was found in AD neurons when compared to age matched controls [65]. To summarize, although again the rates of aneuploidy and which chromosomes are afected difer between studies, the overall trends suggest that aneuploidy might be increased in AD [66].…”
Section: Origin Of Aneuploid Cells In the Brainmentioning
confidence: 77%
“…All of these single cell sequencing studies use cells of which the chromosome copy numbers are known as validation of the method: human male trisomy 21 ibroblasts [82], human male trisomy 18 neurons [81], mouse trisomy 16 brain cells [87] and human female trisomy 21 neurons [66]. In each case, the known aneuploidy as well as the correct number of X chromosomes, male or female, was detected with 100% accuracy, conirming the sensitivity of single cell sequencing.…”
Section: Low Levels Of Aneuploidy Found In the Brain Using Single Celmentioning
confidence: 82%
See 2 more Smart Citations